Pengembangan Potensi Sagu sebagai Pangan Lokal dalam Upaya Mewujudkan Desa Mandiri Pangan di Desa Tuada, Kabupaten Halmahera Barat - Albaar, Nurjanna; Hasbullah, Hasbullah; Rasulu, Hamidin; Fatmawati, Mila; Gunawan, Gunawan; Kamaluddin, Abdul Kadir; Fahri, Johan (Jurnal Pertanian Khairun, 2025)
The development of sago as a local food resource in Tuada Village, West Halmahera Regency, aimed at realizing a self-sufficient food village based on local potential. The main activities include strengthening the capacity of the Marimoi MSMEs in managing sago processing businesses, which enables the community to improve their entrepreneurial skills and enhance the economic value of sago. Education on the application of Good Manufacturing Practices (GMP) was provided to ensure food quality and safety, allowing sago-based products to meet higher market standards. In addition, knowledge transfer on innovative processing techniques has been carried out to expand the variety of sago products, such as instant flour, sago-based macaroni, and sago egg snacks, which significantly increase added value and consumer appeal. The program also emphasizes strengthening community economic institutions through collaborative product marketing strategies and the utilization of digital technology, thereby expanding market reach and reinforcing the position of local products. The technologies applied include hard technologies, such as modern processing equipment, and soft technologies, including business management, packaging, and effective promotion strategies. Furthermore, feasibility studies on household-scale sago flour production and product diversification indicate positive outcomes from technical, financial, and socio-economic perspectives, providing a strong foundation for sustainable business development. Overall, the integration of these initiatives demonstrates that sago development not only contributes to local food security but also plays a significant role in improving community welfare and strengthening the village economy in a sustainable and independent manner.